The Status of Micro, Small, and Medium-sized Enterprises for People with Disabilities in Tanzania: A Scoping Review - Kuluchumila, Revocatus C; Chuwa, Gasper (Khwopa Journal, 2025)
The present scoping review aimed to establish the status of Micro, Small, and Medium-sized Enterprises (MSMEs) for people with disabilities in Tanzania. The PCC (Population or participants/Concept/Context) framework assisted in identifying the main concepts in the scoping research and its fundamental main question. Sixty published research articles and eight grey literatures were included. Themes from the reviewed literature include: opportunities for people with disabilities to obtain funding; entrepreneurial skills possessed by people with disabilities; availability of micro-credits; and business policies in support for people with disabilities. Content and thematic analysis methods were used for data analysis. Findings revealed that people with disabilities faced numerous challenges, including poor infrastructure, raising capital, and poor support from stakeholders. Other challenge includes, low understanding to promote the growth of their organisations.  Research findings likewise found that the majority of persons with disabilities lacked entrepreneurship skills. Research findings similarly revealed that small cash flow, poor accounting practices, inadequate credit history, and high transaction costs hindered credit accessibility by MSMEs. Furthermore, findings indicated that high default rates and a lack of collateral limited financial institutions to lend to MSMEs. Moreover, research findings revealed that the majority of organisations did not consider the need for visually impaired persons to use Information and Communication Technology due to the high cost. Generally, MSMEs for people with disabilities in Tanzania were too depressed. Special training programs were recommended to people with disabilities so as to impart competencies and behavioural change in starting and running businesses. Future research is needed to be done in Tanzania about persons with disabilities in the indigenous community, the Maasai, on their engagement in entrepreneurship.